(untitled) (Tempo e Argumento, 2010)
This article analyzes the political trajectory of the Center of Studies, Documentation and Popular Information of Criciúma (CEDIP) since its establishment, in 1983, until the late 1980s. For that, the political situation of the city, besides the articulations the Centre mantained with the Partido dos Trabalhadores, CUT, Neighborhood Associations and the Catholic Church, was observed.